Parent values and preferences underpinning treatment decision-making in poor-prognosis childhood cancer: a scoping review - Helen Pearson H; Gemma Bryan; Catherine Kayum; Faith Gibson; Anne-Sophie Darlington (BMC, 2022)
Abstract Background Parents of children who are diagnosed with a poor-prognosis cancer want to be involved in making treatment-related decisions for their child. They often make repeated decisions depending on their child's response to treatment and can experience decisional regret as a consequence. Understanding parent values and preferences when making treatment-related decisions may help enhance discussions with healthcare professionals and identify additional ways of providing support to this parent population. Objectives To explore parent values and preferences underpinning treatment decision-making for children receiving cancer-directed therapy for a poor prognosis cancer. Methods A scoping review of research literature and systematic reviews from qualitative, quantitative, and mixed methods studies was conducted following Joanna Briggs Institute methodology. Articles which included parents of a child who received cancer-directed therapy for a poor-prognosis childhood cancer, under the age of eighteen years were considered. Four electronic databases were searched (CINAHL, Medline, PsychINFO, Web of Science Core Collections). Reference and citation lists of all included full-text articles were also searched. Summative content analysis was used to synthesise findings and develop themes. Results Twelve articles were included. Parent decision-making was affected by underpinning factors: hope for a cure, fear of their child dying and uncertainty. Influencing factors: opinions of others, child's wishes, and faith and religion had the potential to inform decision-making processes. Parents valued having enough time, being a good parent and being involved in decision-making. Preferences within these values varied resulting in the potential for conflict and 'trade-offs' in making decisions. Conclusions Parent decision-making in poor-prognosis childhood cancer is complex and extends beyond values and preferences. Underpinning factors and values are consistent through the decision-making process with influencing factors and preferences varying between parents. Preferences can conflict when parents want to continue cancer-directed therapy whilst maintaining their child's quality of life or can change depending on a parents' cognitive state as they realise cure might be unlikely.